Downstaging and laparoscopic hepatectomy plus intraoperative radiofrequency ablation for the treatment of initially unresectable multifocal hepatocellular carcinomas - Wang, Jianjun; Luo, Hua; Yi, Long; Yang, Pei; Zeng, Xintao (Frontiers in Surgery, 2024)
Background: Using TKIs plus anti-PD-1 antibodies combined with TACE in the treatment of patients with initially unresectable multiple HCCs has a high tumour response rate, and using laparoscopic hepatectomy (LH) combined with intraoperative RFA for radical treatment of multiple HCCs after successful downstaging treatment has not been reported.Consecutive patients with multiple HCCs (≤4 lesions) who were downstaged with TKIs plus anti-PD-1 antibodies combined with TACE were analysed.Imaging examinations were performed monthly, and RECIST v1.1 criteria were used to evaluate treatment effect and resectability.Results: Forty-five consecutive patients with multiple HCCs who met the inclusion criteria received downstaging treatment with TKIs plus anti-PD-1 antibodies combined with TACE. Nine patients were successfully downstaged and met the R0 resection criteria, and 8 patients underwent surgery. Among the patients, 5 patients had BCLC stage C, and 3 patients had BCLC stage B. There were 2 lesions in 5 patients, 3 lesions in 2 patients, and 4 lesions in 1 patient. The average size of the main HCC was 8.5 cm (range: 5.4-9.1 cm), and the diameter of the remaining HCCs was 1.6 cm (range: 0.8-2.9 cm). The average time from the start of downstaging therapy to surgery was 81 days (range: 60-210 days). All 8 patients underwent LH of the main HCC, and the remaining HCCs were targeted with RFA. The mean operation time was 220 minutes (range 150-370 minutes), the average intraoperative blood loss was 260 ml (range 100-750 ml), there was no case conversion to laparotomy, and the average postoperative hospital stay was 9 days (range 7-25 days). The incidence of postoperative complications was 37.5% and there were no deaths. The average follow-up time was 18.2 months (range 6.1-22.4 months), 5 patients survived tumour-free, 2 patients had tumour recurrence, and 1 patient died.After successful downstaging of multiple HCCs by treatment with TKIs plus anti-PD-1 antibodies and TACE, LH combined with RFA for radical surgery is safe and feasible, and the treatment effect is satisfactory. It is worthy of clinical reference, and its long-term effects require further research for confirmation.